中国需要怎样的粮食安全战略？ - Guoqiang, Cheng (2015)
Presentation by Cheng Guoqiang, Director General and Research Fellow, International Cooperation Department, Development Research Center of the State Council, delivered on May 13 at Peking University. The event, “New Normal for Economic Growth, Agriculture, Food and Nutrition Security,” was organized by IFPRI and its co-hosting partners, the Chinese Academy of Agricultural Sciences (CAAS) and National School of Development of Peking University.